Combating corruption: International standards and national practice - Topchii, Vasyl Vasylovych; Zadereiko, Svitlana; Didkivska, Halyna Vasylivna; Bodunova, Olesia Mykolaivna; Shayturo, Olga (Florencia: Primmate, 2022)
The purpose of the article is to study modern standards and practice of combating corruption, as well as international and legal documents that are the cause for the existance of different approaches in understanding corruption. The main objectives of the article are to clarify the efficiency of modern well-known indicators that assist in determining the level of corruption in the country; to scientifically substantiate the principles for raising the efficiency of international cooperation in combating corruption within government; to analyze international acts of declarative and binding nature. During the study, general scientific methods of analysis and synthesis, a historical and systemic approach were used. Political analysis was widely used, descriptive and comparative analysis was accomplished. It has been concluded that the states must comply with international norms governing the fight against corruption in order to maintain the global law and order and combating corruption in the world, and in particular in Ukraine. It has been proved that it is necessary to establish more precise criteria for determining the level of corruption than currently existing ones in order to increase the effectiveness of international cooperation in combating corruption in government. Suggestions aimed at combating corruption at the international level have been formulated.

Мета статті – дослідити сучасні міжнародні стандарти та практику боротьби з корупцією, а також міжнародно-правові документи, які є причиною існування різних підходів до розуміння корупції. Основні завдання статті: з’ясувати ефективність сучасних загальновідомих показників, за якими визначається рівень корупції в державі; науково обґрунтувати засади для підвищення ефективності міжнародної співпраці по боротьбі з корупцією в органах влади; проаналізувати міжнародні акти декларативного та загальнообов’язкового характеру. Під час дослідження використовувалися загальнонаукові методи аналізу та синтезу, історичний та системний підхід. Широко використовувався політичний аналіз, здійснено описовий та порівняльний аналіз. Зроблено висновок, що для підтримки глобального правопорядку та боротьби з корупцією у світі, і зокрема в Україні, держави повинні дотримуватися міжнародних норм, що регулюють боротьбу з корупцією. Доведено, що для підвищення ефективності міжнародної співпраці по боротьбі з корупцією в органах влади необхідно встановити більш точні критерії визначення рівня корупції, ніж існуючі сьогодні. Сформульовано пропозиції, спрямовані на подолання корупції на міжнародному рівні.
Keywords: corruption; counteraction; international standards; anti-corruption; international legislation; корупція; протидія; міжнародні стандарти; боротьба з корупцією; міжнародне законодавство